2017
DOI: 10.1021/acsami.7b13947
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rubidium Incorporation on the Structural, Electrical, and Photovoltaic Properties of Methylammonium Lead Iodide-Based Perovskite Solar Cells

Abstract: We report the electrical properties of rubidium-incorporated methylammonium lead iodide ((RbMA)PbI) films and the photovoltaic performance of (RbMA)PbI film-based p-i-n-type perovskite solar cells (PSCs). The incorporation of a small amount of Rb (x = 0.05) increases both the open circuit voltage (V) and the short circuit photocurrent density (J) of the PSCs, leading to an improved power conversion efficiency (PCE). However, a high fraction of Rb incorporation (x = 0.1 and 0.2) decreases the J and thus the PCE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 44 publications
(56 reference statements)
3
43
0
Order By: Relevance
“…It can be seen that the V oc was immediately increased from 0.92 V (average) to over 1 V due to spiro-OMeTAD + formation. According to the definition, the V oc is related to both light-generated current and saturation current [28], as shown by Equation (1):…”
Section: Resultsmentioning
confidence: 99%
“…It can be seen that the V oc was immediately increased from 0.92 V (average) to over 1 V due to spiro-OMeTAD + formation. According to the definition, the V oc is related to both light-generated current and saturation current [28], as shown by Equation (1):…”
Section: Resultsmentioning
confidence: 99%
“…Park et al unveiled that incorporating excessive Rb + in MAPbI 3 will lead to significant Rb + segregation. [45] Hu et al also found that the Rb + accumulates at the TiO 2 /perovskite interface in the 5% Rb doped FA 0.83 MA 0.17 Pb(I 0.83 Br 0.17 ) 3 perovskite. [46] On the contrary, the Cs + is evenly distributed within the 5% Cs doped FA 0.83 MA 0.17 Pb(I 0.83 Br 0.17 ) 3 perovskite films.…”
Section: Cation Distribution In Mhpmentioning
confidence: 94%
“…The built-in potential and defect density could be obtained from the voltage intercepts and from the slope, respectively, by fitting the C À2 with respect to the bias in the C s region. In the Mott-Schottky plot, C À2 and V are related by [38][39][40][41] 1…”
Section: Capacitance-voltagementioning
confidence: 99%